Role of Ionic Liquids in Composites in Analytical Sample Preparation - Adrián Gutiérrez-Serpa; Patricia I. Napolitano-Tabares; Jakub Šulc; Idaira Pacheco-Fernández; Verónica Pino (Separations, 2020)
Ionic liquids (ILs) are a group of non-conventional salts with melting points below 100 °C. Apart from their negligible vapor pressure at room temperature, high thermal stability, and impressive solvation properties, ILs are characterized by their tunability. Given such nearly infinite combinations of cations and anions, and the easy modification of their structures, ILs with specific properties can be synthesized. These characteristics have attracted attention regarding their use as extraction phases in analytical sample preparation methods, particularly in liquid-phase extraction methods. Given the liquid nature of most common ILs, their incorporation in analytical sample preparation methods using solid sorbents requires the preparation of solid derivatives, such as polymeric ILs, or the combination of ILs with other materials to prepare solid IL-based composites. In this sense, many solid composites based on ILs have been prepared with improved features, including magnetic particles, carbonaceous materials, polymers, silica materials, and metal-organic frameworks, as additional materials forming the composites. This review aims to give an overview on the preparation and applications of IL-based composites in analytical sample preparation in the period 2017–2020, paying attention to the role of the IL material in those composites to understand the effect of the individual components in the sorbent.